Transaksi Digital Perbankan dan Dampaknya dengan Perekonomian Indonesia - Yusuf, Dina Yuliana; Kristiyanto, Sony (Economie: Jurnal Ilmu Ekonomi, 2022)
The process of analyzing the effect of short-term and long-term non-cash payment systems on economic growth in Indonesia in the form of P.D.B. Non-cash payment systems are represented by debit/debit cards, credit cards/credit cards and electronic money/e-money using time series data (January 2010 – December 2020) with E.C.M.(Error Correction Model). The conclusion obtained shows that the transaction volume of debit/debit cards, credit cards/credit cards and electronic money/e-money in the short term/short term has no effect on economic growth in Indonesia and the volume of card transactions in the long term/long term has negative relationship with economic growth in Indonesia.